Boy kills world [videorecording (Blu-Ray + DVD)] - Remmers, Arend, 1981-; Smith, Tyler Burton; Skarsgård, Bill; Rothe, Jessica; Dockery, Michelle, 1981-; Gelman, Brett, 1976-; Mustafa, Isaiah, 1974-; Ruhian, Yayan, 1968-; Crovetti, Cameron; Crovetti, Nicholas; Copeland, Quinn; Koji, Andrew, 1987-; et al. (Lionsgate, 2024)
Driven by his inner voice -- one which he chose from his favorite childhood video game -- and guided by the spirit of his little sister -- who he saw murdered in front of him -- a deaf-mute boy trains with a mysterious shaman to become an instrument of death. Convinced the ruling family massacred his family, Boy is single-minded but soon falls in with a desperate resistance group, using them to infiltrate the Van Der Koy compound to exact his bloody revenge. As he gets closer to each family member, truths revealed shake his focus, but he won't rest until the matriarch is eradicated.